2016
DOI: 10.1021/jacs.5b12189
|View full text |Cite
|
Sign up to set email alerts
|

Encapsulation of a Metal–Organic Polyhedral in the Pores of a Metal–Organic Framework

Abstract: A new and efficient hydrophilicity-directed approach (HDA) is developed to encapsulate large guest molecules beyond the aperture size limitation in the nanospace of metal-organic frameworks (MOFs), as exemplified by the self-assembly of a metal-organic polyhedral (MOP) M6L4 into MIL-101. This strategy is based on the different hydrophilicities between inner and outer surfaces of the preformed MOF that may direct the self-assembly of the MOP in the MOF pores by using a two-solvent system. Importantly, as the MO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
84
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(86 citation statements)
references
References 58 publications
2
84
0
Order By: Relevance
“…The 13 C solid‐state NMR spectrum of CB6 shows three peaks (Figure b) at δ =155.05, 70.42, and 52.42 ppm, which were attributed to the C=O, CH, and CH 2 groups in CB6 . In contrast, solid MIL‐101 shows no obvious NMR signals because of the paramagnetic Cr centers . As expected, CB6@MIL‐101‐36 also shows the characteristic peaks of CB6.…”
Section: Resultssupporting
confidence: 56%
See 1 more Smart Citation
“…The 13 C solid‐state NMR spectrum of CB6 shows three peaks (Figure b) at δ =155.05, 70.42, and 52.42 ppm, which were attributed to the C=O, CH, and CH 2 groups in CB6 . In contrast, solid MIL‐101 shows no obvious NMR signals because of the paramagnetic Cr centers . As expected, CB6@MIL‐101‐36 also shows the characteristic peaks of CB6.…”
Section: Resultssupporting
confidence: 56%
“…The smaller cage has pentagonal windows with an aperture of approximately 1.2 nm, while the larger cage possesses both pentagonal and hexagonal windows with an opening of 1.5 nm (Scheme b). As the molecular size (1.44 nm) of CB6 is smaller than the hexagonal window size (1.5 nm), and the inner surface of MIL‐101 is more hydrophilic than the outer surface, CB6 molecules could be readily encapsulated in the larger pores of MIL‐101 by incipient‐wetness impregnation (Scheme c). The proper molecular size is, of course, important for the guest impregnation.…”
Section: Resultsmentioning
confidence: 99%
“…[18] Thes maller cage has pentagonal windows with an aperture of approximately 1.2 nm, while the larger cage possesses both pentagonal and hexagonal windows with an opening of 1.5 nm (Scheme 1b). As the molecular size (1.44 nm) of CB6 is smaller than the hexagonal window size (1.5 nm), and the inner surface of MIL-101 is more hydrophilic than the outer surface, [19] CB6 molecules could be readily encapsulated in the larger pores of MIL-101 by incipient-wetness impregnation (Scheme 1c). Thep roper molecular size is,o fc ourse,i mportant for the guest impregnation.…”
Section: Resultsmentioning
confidence: 99%
“…Thehighly ordered lattice and tunable pore sizes of MOFs have been used to accommodate polyoxometalates, [17] metal complexes, [18] metal-organic polyhedra, [19] metal nanoparticles, [20] and ionic liquids [21] as functional guests.T hese MOFbased host-guest composites have been obtained by various methods including incipient-wetness impregnation. [22] However,t ot he best of our knowledge,t here is no report on fabricating functional porous hybrids by encapsulating aPOC in the pores of aMOF.Wedemonstrate here that POC@MOF is anew "host-in-host" system with enhanced performance in CO 2 adsorption and CO 2 /N 2 ,CO 2 /CH 4 separation up to 1bar, ap roof of principle for the impetus to develop further POC@MOF materials.…”
Section: Introductionmentioning
confidence: 99%
“…In another study,Q iu et al demonstrated ane fficient hydrophilicity-directeda pproach (HDA) to encapsulate MOP M 6 L 4 (one of the most commonly representativeo ctahedral MOPs), whichi sl arger in size than the apertures of the mesoporous host MOF,M IL-101( Cr). [87] The HDA approach, based on hydrophilicity differences between inner and outer surfaces of the MOFs, drives the self-assembly of MOPs by the use of two-solvents ystemsw ith different hydrophilicities. The catalytic activity of the MOPs in M 6 L 4 &MIL-101 composites increased drastically,a nd the performance retention overafew cycles confirmed no obvious aggregation of the cages.…”
Section: Mops Dispersed In Ap Orous Matrixmentioning
confidence: 99%